The Analysis Of Science Learning Problems At SMPN 1 Suwawa Timur - Tirtawaty Abdjul; Mentari Br Sembiring; Nurhadi Prayogo Sabia; Ranselengo, Denada (International Journal of Technology and Education Research, 2025)
This study aims to thoroughly analyze the problems encountered in the Natural Science (IPA) learning process at SMPN 1 Suwawa Timur, considering the 21st-century curriculum demands that require the development of students' scientific attitudes and skills through direct experience. This research employs a descriptive qualitative approach, where data was collected through a closed questionnaire administered to 32 students of class IX A and in-depth interviews with the IPA subject teacher. The analysis results identified two major interconnected issues: (1) low student motivation and scientific attitude, and (2) sub-optimal utilization of school facilities and infrastructure. The low student learning motivation was confirmed by the teacher as a crucial obstacle, which ironically occurs despite the school having complete laboratory facilities. The root problem was found in the lack of teacher knowledge and professional competence in operating and utilizing laboratory equipment for practical activities. It is concluded that the minimal implementation of practical work due to limitations in teacher competence is the main factor contributing to low student motivation and learning achievement. Therefore, this study recommends the necessity of continuously enhancing teacher competence related to laboratory facility utilization to optimize the quality of the IPA learning process in the school.